2001
DOI: 10.1063/1.1351519
|View full text |Cite
|
Sign up to set email alerts
|

Patterning ferromagnetism in Ni80Fe20 films via Ga+ ion irradiation

Abstract: We demonstrate that focused Ga+ ion irradiation can comprehensively modify the ferromagnetic properties of Ni80Fe20 thin films. Magneto-optic Kerr effect measurements at room temperature and magnetoresistance measurements at temperatures between 1.5 and 270 K characterized the irradiation effects. Irradiation steadily reduced the films’ room temperature coercivity, and a dose of 1.0×1016 ions/cm2 at 30 keV was found sufficient to cause a loss of ferromagnetism at room temperature in films of thickness up to 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 12 publications
(5 reference statements)
1
36
0
Order By: Relevance
“…[4][5][6][7] It has been used to modify and tune the local magnetic properties in magnetic systems. [8][9][10][11][12] This approach has been used to realize artificial domain structures 13 and locally control the domain wall dynamics. 14 In spite of the enormous wealth of FIB applications, there are few studies concerned with the details of the physical process manifest within the materials during FIB exposure.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] It has been used to modify and tune the local magnetic properties in magnetic systems. [8][9][10][11][12] This approach has been used to realize artificial domain structures 13 and locally control the domain wall dynamics. 14 In spite of the enormous wealth of FIB applications, there are few studies concerned with the details of the physical process manifest within the materials during FIB exposure.…”
Section: Introductionmentioning
confidence: 99%
“…However, although a range of ion species can be incorporated into FIBs, most commercial systems are limited to Ga þ ions. Earlier work suggested that direct implantation of Ga þ at high fluences is the main mechanism for modifying the magnetic properties 22 and that moderate fluences can tune the coercivity, saturation magnetization and anisotropy field in NiFe/Au bilayers. 23 In bilayered or multilayered ferromagnetic/nonmagnetic (FM/NM) systems, low-dose FIB irradiation could be used to induce interfacial doping providing a route to locally modify the magnetic properties without substantial structural changes or damage.…”
mentioning
confidence: 99%
“…Nevertheless, Ga ion implantation can be minimized by optimizing the FIB process. In fact, Ga ion implantation is another way in which device structures can be created or a material's properties modified in a relatively controlled way; for example, an FIB system has been used to modify the interface anisotropy of magnetic multilayer systems [45,46] or the volume magnetization [47]. More constructively, Ga ion implantation has now been used to create artificial magnetic domains, which has enabled the angular dependence of magnetic domain-wall resistance to be measured [48].…”
Section: (B) Focused Ion Beam Device Fabricationmentioning
confidence: 99%